Penalty responsibility of juveniles in the Republic of Srpska - Grbić-Pavlović Nikolina (Temida)
The youngest members of organized society, more intensive than ever enter the circle of those whose behavior is deviant. Juvenile delinquency is a social problem, which recently experienced an expansion in all modern countries, including Bosnia and Herzegovina and the Republic of Srpska. Considering the fact that juvenile delinquency includes lighter criminal conducts, such as, for example misdemeanors, in this paper a position of juveniles when they are a perpetrators of misdemeanors will be analyzed. Also, the paper will statistically show the number of misdemeanors in the field of public peace and order that juveniles conducted in the Republic of Srpska in the period 2004-2009.